The Effect of Black Cumin Seed Oil on Alanine Aminotransferase Levels which are Influenced by Nutritional Status in Active Smokers - Arif Santoso; Titiek Hidayati; Akrom Akrom; Laela Hayu Nurani (PHARMACY: Jurnal Farmasi Indonesia (Pharmaceutical Journal of Indonesia), 2021)
Black cumin seed oil (BCSO) has the main compound thymoquinone which is thought to have hepatoprotective activity through an antioxidant mechanism. Exposure to cigarette smoke can cause cellular oxidative stress which is the key to the inflammatory process of liver cells and an increase in the activity of the Alanine aminotransferase (ALT) enzyme. Vitamin C and folic acid are nutrients that affect ALT levels through antioxidant activity. The main objective of this study was to see the effect of BCSO administration on ALT levels which were influenced by the intake of vitamin C and folic acid in healthy respondents who were active smokers for 30 days. This study used a single-blind Randomized Controlled Trial (RCT) method, with a total of 39 test subjects divided into four groups. Group 1 received 3x1 placebo, group 2 received BCSO 3x1, group 3 received BCSO 3x2, group 4 received BCSO 3x3. Investigation based on the ANOVA test, it turned out that there was no significant difference in the mean ALT levels in both the placebo group and the treatment group with p value = 0.452. For the p value of the intake of vitamin C and folic acid were 0.359 and 0.669, respectively. Based on the results of the study showed that the administration of BCSO for 30 days had no significant effect on the average activity of ALT in healthy active smokers and there was no significant difference in the intake of vitamin C and folic acid.